Response Characteristics of Array Induction Logging in Fractured Formation - GUO Hongbo; GUO Yunlong; ZHOU Lei; CAO Fuhua (Cejing jishu)
The fracture scale of fractured formation is different, the forward modeling of logging response is difficult, and the quantification and characterization of fracture parameters are difficult. Formation microscanner image (FMI) logging and dual laterolog logging are important means to identify and evaluate fractured formation, but the fracture response simulation of array induction logging is difficult and the response characteristics are not clear. In this paper, the response characteristics of fractured formation array induction logging are studied systematically, and a new simplified model fast forward modeling method is proposed. Firstly, the three-dimensional strict forward modeling model is equivalent to the layered model of one-dimensional dipole emission and point reception, and three models of single crack, multiple crack and parallel plate crack with equal spacing are established respectively. Secondly, the subarray response of fractured strata and the synthetic signal response are realized by the simplified model fast forward modeling method. Finally, the response characteristics of different fracture models are compared, and the difference of response of array induction logging to fractured formation is investigated. The results show that in the case of a single low-resistance fracture, the smaller the crack inclination, the larger the contrast between bedrock and crack resistivity and the larger the crack opening, the larger the response amplitude and the more obvious the change. Array induction logging is insensitive to high resistance fracture response. When there are multiple cracks, the number of cracks will affect the shallow detection curve. When the cracks are close, the synthetic curve cannot distinguish the number of cracks. These response rules provide a new research idea and theoretical basis for identifying fractured reservoirs.